ARABIDOPSIS ATMKK1 KNOCKOUT MUTANT FLOWERS UNDER SHORT DAY CONDITIONS - Chad CONROY; Khadijah M. NIZAM; Tim XING (Journal of Plant Development)
There are a variety of conditions that regulate flowering time in Arabidopsis, but there are no reported instances mitogen-activated protein kinase pathways playing a decisive role in flowering time. Our work has indicated that when long-day plant Arabidopsis mitogen-activated protein kinase kinase 1 (AtMKK1) was knocked out, Arabidopsis plants flowered under short day conditions. Possible mechanisms are discussed.